Multiphase modeling of the impact of groundwater pore velocities on DNAPL migration in the multi-aquifer formation of Rho, Italy - Erning, Katharina; Dahmke, Andreas; Schäfer, Dirk (Italian journal of engineering geology and environment, 2013)
2D multiphase modeling of DNAPL behavior in a realistic subsurface morphology of the former industrial site of Chimica Bianchi provided evidence that moderate groundwater pore velocities are sufficient to transport a TCE phase body over large distances in the downstream direction. In the investigated model set-up, the DNAPL was found to be able to counteract the morphological effects of a slope of 2.5° and leave depressions and trenches. The displacement depends directly on the encountered hydraulic pressure regime. Moreover, only materials with a hydraulic conductivity lower than 1 × 10-9 m/s were impermeable to the DNAPL over a time period of 75 years. The modeling approach presented in this study provides an explanation for the inaccurate, or often even unknown, position of DNAPL source zones at many industrial sites. Furthermore, by narrowing down possible locations, the simulations proved to be a valuable tool for both investigation and remediation activities of DNAPL-contaminated sites.